Nazi bomb kills seventy Spanish children (press cutting) - Holmes, Walter M.
010-0001-001 Thursday, November 12, 1936 DAILY WORKER 5 She's English. She plays in peace now. But Fascist aggression, unchecked, carries its threat of death for our children, too. Twelve days ago THEY played as SHE does- NAZI BOMB KILLS SEVENTY SPANISH CHILDREN Why We Print This Page BY WALTER HOLMES WE DISCUSSED LONG AND SERIOUSLY WHETHER OR NOT TO PRINT THIS AWFUL PAGE. PREVIOUSLY, DURING THIS SPANISH CIVIL WAR, WE HAVE RECEIVED PICTURES SHOWING AUTHENTICATED EXAMPLES OF THE MUTILATION OF MEN AND WOMEN BY FRANCO'S SAVAGE FORCES. We have refrained from publishing these because it seemed that mere horror would not serve our great purpose, which is to harden the determination to fight Fascism and defend democracy. BUT THE PICTURES ON THIS PAGE ARE NOT OF MERE HORROR. THEY TELL THE TALE OF THE MOST FEARFUL SIDE OF THE CONFLICT INTO WHICH FASCISM HAS HURLED THE SPANISH PEOPLE. They do not tell the full tale. They only hint at the reality. I write this explanation because it has been my lot to see death reap its mass harvest of peaceful populations in these modern wars of aeroplanes and poison-gas. I HAVE SEEN DAINTY DOLL-LIKE CHINESE CHILDREN AND COMICAL LITTLE MONGOLS REDUCED TO GHASTLY REMNANTS SUCH AS YOU SEE ON THIS PAGE. I HAVE SEEN MUSSOLINI'S BOMBS COME HISSING DOWN AND BLOT OUT THE WARM, BROWN NAKED LITTLE BODIES OF ABYSSINIAN CHILDREN AS THEY PLAYED ROUND THEIR NATIVE HUTS. But I know it does no good merely to tell tales of horror. War has abominations so foul that they are only for those who have had to see them. Why, then, do we print these pictures. To shock? Certainly. But to shock all who look at them into realising that these dead children are the cost of brutal, militaristic aggression against peaceful people. Planes and pilots from Mussolini and Hitler did this dreadful work. And behind them the whole machine of Fascism which capitalism has made as its last defence in Europe. This same price of death will have to be paid until the death-dealers are themselves destroyed. Look on these pictures and resolve, blow for blow, man for man shall be our reply until the arms of democracy have won the only way to peace. WHAT HAPPENED . .. . . . when death fell among 100 schoolchildren playing in a sunlit street of Getafe, near Madrid, on October 30. Three of Franco's Nazi Junker planes flew over the little town. They dropped a bomb on the street where the children played. That bomb killed 70 schoolchildren. A British reporter wrote: "I saw parents searching for bodies. The bodies had been placed in a small delivery lorry belonging to local grocers. I tried to look in, but the sight was too gruesome." Photos show the broken bodies of Fascism's little victims, and (below, left) the dead children lying later in the school which they had attended. 292/946/10/1(ii)